MicroRNA-195-3p inhibits cyclin dependent kinase 1 to induce radiosensitivity in nasopharyngeal carcinoma. Issue 1 (1st January 2021) - Xie, Fuchuan; Xiao, Wei; Tian, Yunming; Lan, Yuhong; Zhang, Chi; Bai, Li
ABSTRACT: MicroRNAs (miRNAs) are revealed to participate in the progression of multiple malignancies, including nasopharyngeal carcinoma (NPC). This work is intended to decipher the function of microRNA-195-3p (miR-195-3p) in regulating the radiosensitivity of NPC cells and its mechanism. MiR-195-3p and cyclin-dependent kinase 1 (CDK1) expressions were detected in NPC tissues and cells using qRT-PCR and Western blot, respectively. Moreover, radiation-resistant cell lines were induced by continuous irradiation with different doses. Furthermore, the CCK-8 experiment, colony formation assay and flow cytometry were utilized to examine the growth, apoptosis and cell cycle of radioresistant cells. Bioinformatics prediction and dual-luciferase reporter gene assay were applied to prove the targeting relationship between miR-195-3p and CDK1 mRNA 3ʹUTR. The data showed that miR-195-3p was remarkably down-modulated in NPC tissues and was associated with increased tumor grade, lymph node metastasis and clinical stage of the patients. MiR-195-3p expression was significantly down-modulated in radiation-resistant NPC tissues and NPC cell lines relative to radiation-sensitive NPC tissues and human nasopharyngeal epithelial cells, while CDK1 expression was notably up-modulated. MiR-195-3p overexpression inhibited the growth of NPC cells, decreased radioresistance, promoted apoptosis, and impeded the cell cycle progression. CDK1 was a target gene of miR-195-3p, and CDK1 overexpression counteracted the effects of miR-195-3p on NPC cell growth, apoptosis, cell cycle progression and radiosensitivity. In summary, miR-195-3p improves the radiosensitivity of NPC cells by targeting and regulating CDK1.